Customer Satisfaction in the Hotel Industry: A Case Study from Makassar City - Muhammad Anas (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study analyzes the impact of service quality on customer satisfaction at Hotel Pantai Gapura Makassar. Five dimensions of service quality were examined: reliability, responsiveness, assurance, empathy, and tangibles. The research was conducted from June to August 2023 with 680 respondents selected through accidental sampling. The analysis method used was multiple regression with validity, reliability, and classical assumption tests. Results show that responsiveness, empathy, and tangibles have a significant positive effect on visitor satisfaction, while reliability and assurance do not have a significant impact. Empathy is the most dominant variable influencing visitor satisfaction with the highest beta value of 0.554. Specifically, the coefficient of responsiveness influence is 0.683 (p<0.05), empathy 0.995 (p<0.05), and tangibles 0.225 (p<0.05). Meanwhile, reliability has a coefficient of -0.217 (p>0.05) and assurance 0.164 (p>0.05), indicating non-significant effects. In conclusion, to enhance visitor satisfaction, Hotel Pantai Gapura Makassar should focus on improving empathy, responsiveness, and tangible aspects of its service. This research contributes to understanding the relationship between service quality dimensions and customer satisfaction in the hospitality industry context.